Poly(4-vinylpyridine)/gold nanoparticle/graphene nanocomposites for enzymatic amperometric biosensor - Jiajia, Long (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Amperometric enzymatic biosensor which consists of recognition element and transduction element, is an important tool in environmental monitoring, health care, food biotechnology. Nanomaterial-modified electrodes of an enzymatic biosensor can immobilize enzyme as well as improve the general performance for the analyte detection, such as sensitivity, stability and response time. In this research, nanocomposites that consist of graphene, poly-4-vinlyridine (P4VP) and gold nanoparticles (AuNPs) were applied as a suitable matrix to immobilize enzyme and also to accelerate electron transfer between the active site of enzyme and surface of electrode. During the fabrication process, the preparation of P4VP/AuNPs nanocomposite was accomplished first through hybridization between gold precursors (Au3+) and pyridine group of P4VP, and then using hydrazine reduction to synthesize gold nanoparticles. After addition of graphene oxide (GO), the resulting P4VP/AuNPs/GO nanocomposites were optimized via cyclic voltammetry (CV) and the R3/GO (R3: P4VP:Au3+ = 1:10) was selected. And then glucose oxidase (GOx) was casted on the P4VP/AuNPs/rGO modified glassy carbon electrode (GCE) using drop casting method. The properties of P4VP/AuNPs and P4VP/AuNPs/GO/GOx were characterized by Fourier transform infrared spectroscopy (FTIR), UV-vis spectroscopy, field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The GCE modified with the P4VP/AuNPs/rGO/GOx showed good eletrocatalytic response to the oxidation of glucose. The fabricated glucose biosensor exhibited a good sensitivity (8.768 uA mM-1 cm-2) and a good stability.